ASSESSMENT OF THE EFFECT OF CARVEDILOL ON THE PERIODONTAL STATUS - Cristina-Maria Gavrilescu; Anca Stan; Roxana Timofte; Maria-Mădălina Bodescu; Paloma Manea; Roxana Barbu; Rodica Ghiuru; Crânguţa Paraschiv (Romanian Society of Oral Rehabilitation, 2015)
Background Oxidative stress plays an important part in the pathogenesis of periodontitis and improving the oxidative status is beneficial for its evolution. Carvedilol is a betablocker that has antiproliferative effects and that inhibits the action of oxygen-free radicals. The aim of this study was to evaluate the effect of carvedilol on the periodontal status. Material and methods 31 patients that were chronically receiving carvedilol for 6 months (group I) were compared regarding their periodontal status with a lot of 12 control patients (that received other types of antihypertensive drugs. The periodontal status was evaluated by measuring gingival index, plaque index and papillary bleeding index. Results The average clinical measurements demonstrated significantly better parameters (P\0.001) in group I compared to group II. Conclusions The average periodontal status of the patients treated with Carvedilol was better, possibly because of its antioxidant effect.